THE EFFECT OF DEEP BACK MASSAGE ON THE INTENSITY OF LABOR PAIN IN THE 1ST ACTIVE PHASE IN PRIMIGRAVIDA MOTHERS AT THE KARTIKA JAYA CLINIC, SAMARINDA PENGARUH DEEP BACK MASSAGE TERHADAP INTENSITAS NYERI PERSALINAN KALA 1 FASE AKTIF PADA IBU PRIMIGRAVIDA DI KLINIK KARTIKA JAYA SAMARINDA - lestari, wiwit indah; Meihartati, Tuti (ITKES Wiyata Husada Samarinda, 2024)
ABSTRACT Labor pain can cause anxiety and fearin patients so that the need for oxygen increases, muscles become tense as wellblood pressure increases, this condition will stimulate catecholamines which cancauses the force of contractions to occur, resulting in parturitionlong Objective: Analyze the effect of deep back massage on pain intensity1st stage of labor active phase in primigravida mother at Kartika Jaya Clinic Samarinda on2021. Method: This research is quasi-experimental in nature. Sample in this researchare 30 respondents of maternity mothers who will give birth at the Kartika Jaya Samarinda Clinic.The sample in this research was purposive sampling, namely data collectionaccording to the considerations made by the researcher. The data obtained was analyzed usingusing dependent t-test. Result: test value 2 Related – Sample (TestWilcoxon) pain scale in the pretest and posttest is p value 0.000 <0.05 so there isThe difference in pain before and after being given the Deep Back Massage method.Conclusion: The results of this study indicate that there is an effect of reducing paingiving birth when given the Deep Back Massage method